2023
DOI: 10.1093/cid/ciad001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Aβ42/Aβ40 Ratios in Older People With Human Immunodeficiency Virus

Abstract: Background As people with HIV (PWH) age, it remains unclear whether they are at higher risk for age-related neurodegenerative disorders, e.g., Alzheimer disease (AD), and if so, how to differentiate HIV-associated neurocognitive impairment from AD. We examined a clinically-available blood biomarker test for AD (plasma Aβ42/Aβ40 ratio), in cognitively-normal (CN) or cognitively-impaired (CI) PWH and people without HIV (PWoH) who were CN or with symptomatic AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Moreover, soluble Aβ42 and Tau/Aβ42 did not correlate with corresponding CSF EV-associated forms. Consistent with these findings, some studies reported no significant difference in Aβ deposition according to HIV serostatus or HAND stage [58,59], while others reported no significant difference in CSF Aβ peptides and p-Tau concentrations between groups stratified by HIV or HAND [26,60]. Unexpectedly, we observed higher CSF Aβ42 levels in PWH compared with HIV− controls; the explanation for this finding remains unclear and warrants further study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, soluble Aβ42 and Tau/Aβ42 did not correlate with corresponding CSF EV-associated forms. Consistent with these findings, some studies reported no significant difference in Aβ deposition according to HIV serostatus or HAND stage [58,59], while others reported no significant difference in CSF Aβ peptides and p-Tau concentrations between groups stratified by HIV or HAND [26,60]. Unexpectedly, we observed higher CSF Aβ42 levels in PWH compared with HIV− controls; the explanation for this finding remains unclear and warrants further study.…”
Section: Discussionsupporting
confidence: 87%
“…An increased CSF Tau/Aβ42 ratio is a biomarker associated with risk of aMCI and AD; increased CSF Tau reflects its release from degenerating neurons while decreased CSF Aβ42 reflects higher amyloid deposition in the brain [ 21 , 22 , 23 , 24 ]. Most studies of aMCI/AD-related biomarkers according to HIV serostatus have not detected a significant increase among PWH compared to the general population [ 11 , 20 , 25 , 26 , 27 ]. Moreover, early neuroinflammation in PWH might have protective effects against Aβ and Tau deposition in the brain [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of cART changed the clinical definition of HAND to a far milder and generally manageable entity, which notably is characterized as reversible and, therefore, fundamentally different from the relentless and progressive nature of AD [ 44 , 45 , 46 , 47 ]. At least some biomarkers observed in cognitively impaired patients with HIV are distinct from AD (e.g., Aβ42/Aβ40 ratios are not reduced in HIV, contrasting with AD) [ 48 ]. Moreover, neuropathological differences have emerged between HAND and AD, including differences in amyloid plaque morphology, which is typically diffuse in HAND, contrasting with AD, which is characterized by dense-core plaques [ 49 ] and where diffuse plaques are considered benign lesions [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed no association of NP with the Aβ42-to-Aβ40 ratio, which has been associated with an increased incidence of AD in HIV-uninfected aging individuals . However, no association of plasma Aβ42-to-Aβ40 ratio in people aged older than 40 years with AD and without HIV compared with similar-aged PLWH who were cognitively normal or who had AD was also reported …”
Section: Discussionmentioning
confidence: 99%
“… 9 However, no association of plasma Aβ42-to-Aβ40 ratio in people aged older than 40 years with AD and without HIV compared with similar-aged PLWH who were cognitively normal or who had AD was also reported. 41 …”
Section: Discussionmentioning
confidence: 99%